PHARMACOLOGICAL PROFILE OF CATHARANTHUS ROSEUS (APOCYNACEAE) - A DETAILED REVIEW - Mallikq, Jony; Chowdhuryq, Hafsha Begum; Faruq, Abdullah Al; Das, Sourav (Asian Journal of Pharmaceutical Research and Development, 2013)
The main goal of this review is to make a proper status of about the pharmacological activity of Catharanthus roseus (Apocynaceae). Catharanthus roseus is a very useful medicinal plants that are growing at the different districts of Bangladesh. The local or bangla name of Catharanthus roseus is Nayantara. Catharanthus roseus is native to the Indian Ocean island of Madagascar. This herb is now common in many tropical and subtropical regions worldwide, including the southern United States. The distinct part this plant may possess different pharmacological activity to the human being. The plant contains about 130 alkaloids, out of which 25 are dimeric in nature. Two of the dimeric alkaloids vinblastine and vincristine mainly present in the aerial parts, have found extensive application in the treatment of human neoplasm. The present article attempts to provide comprehensive information on pharmacological properties of Catharanthus roseus for further potential research. All the information has been collected from the published research paper on Catharanthus roseus as for the sake of future phytochemical or pharmacological research on it.